Breaching the Barrier: Quantifying Antibiotic Permeability across Gram-negative Bacterial Membranes. Issue 18 (23rd August 2019) - Cama, Jehangir; Henney, Abby Mae; Winterhalter, Mathias
Abstract: The double-membrane cell envelope of Gram-negative bacteria is a sophisticated barrier that facilitates the uptake of nutrients and protects the organism from toxic compounds. An antibiotic molecule must find its way through the negatively charged lipopolysaccharide layer on the outer surface, pass through either a porin or the hydrophobic layer of the outer membrane, then traverse the hydrophilic peptidoglycan layer only to find another hydrophobic lipid bilayer before it finally enters the cytoplasm, where it typically finds its target. This complex uptake pathway with very different physico-chemical properties is one reason that Gram-negative are intrinsically protected against multiple classes of antibiotic-like molecules, and is likely the main reason that in vitro target-based screening programs have failed to deliver novel antibiotics for these organisms. Due to the lack of general methods available for quantifying the flux of drugs into the cell, little is known about permeation rates, transport pathways and accumulation at the target sites for particular molecules. Here we summarize the current tools available for measuring antibiotic uptake across the different compartments of Gram-negative bacteria. Graphical abstract: Unlabelled Image Highlights: Review of techniques to study antibiotic permeation in gram-negative bacteria Latest developments in mass spectrometry and single-cell level drug uptake studies Innovations in model membrane assays including electrophysiology and microfluidics